Basmajian-type inequalities for maximal representations - Fanoni, Federica; Pozzetti, Maria Beatrice (Arxiv, 2016)
For suitable metrics on the locally symmetric space associated to a maximal representation, we prove inequalities between the length of the boundary and the lengths of orthogeodesics that generalize the classical Basmajian's identity from Teichmueller theory. Any equality characterizes diagonal embeddings.
Last revised 14 Dec 2017
Gesehen am 21.03.2018